A study on the information needs and information-seeking behavior of pregnant women in Barangay UP Campus, Quezon City - Bartolome, Femush Gwynn T. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Pregnant women are vulnerable to various health and environmental risks which is why these women should be provided with quality health and services that would enable a safe pregnancy and delivery for them and for their child. According to Aaronson, Mural, and Pfoutz (1988), pregnancy causes physical, emotional, and social changes to a woman which may induce the need for new information to properly adjust to these new circumstances. In connection to this, information services should also be provided to pregnant women to empower them in making the right choices regarding their maternal health.